Rise: A Pop History of Asian America from the Nineties to Now - Yang, Jeff; Yu, Phil; Wang, Philip; Kuo, Julia (Boston : Mariner Books, an imprint of HarperCollinsPublishers, 2022)
"'RISE' is a love letter to and for Asian Americans--a vivid scrapbook of voices, emotions, and memories from an era in which [their] culture was forged and transformed, and a way to preserve both the headlines and the intimate conversations that have shaped [their] community into who [they] are today"--Provided by publisher.
Keywords: Asian Americans -- History; Asian Americans in mass media; Asian Americans in popular culture